Spatial distribution of roots and nutrients in soil under rubber plantations in Tripura - Philip Varghese; Krishnakumar A K; Pothen Jacob; Rao D V K N; Varghese Mary; Vinod K K (Indian Journal of Natural Rubber Research, 1996)
Spatial distribution of roots and nutrients in the horizontal and vertical planes was assessed in a five year old rubber plantation in Tripura, India. Root concentration was seen in the top 18 cm layer. Horizontally the roots were found upto 200 cm away from the plant base. Nutrient concentrations were also higher in the top layer than in the lower layers. There was a positive correlation between available phosphorus and fine root concentration suggesting influence of phosphorus in root development.
Keywords: Available nutrients; Available nutrients; Hevea brasiliensis; Hevea brasiliensis; Root length density; Root length density; Spatial distribution; Spatial distribution; Tripura; Tripura